2016
DOI: 10.1007/s11325-016-1373-5
|View full text |Cite
|
Sign up to set email alerts
|

Support vector machines for automated snoring detection: proof-of-concept

Abstract: Background Snoring has been shown to be associated with adverse physical and mental health, independent of the effects of sleep disordered breathing. Despite increasing evidence for the risks of snoring, few studies on sleep and health include objective measures of snoring. One reason for this methodological limitation is the difficulty of quantifying snoring. Conventional methods may rely on manual scoring of snore events by trained human scorers, but this process is both time- and labor-intensive, making the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Previous studies mainly focused on analyzing the characteristics of snoring, or distinguishing snoring from non-snoring sounds. One study reported that the classification performance of human visual scorers and a machine learning algorithm was similar in terms of automatically identifying snoring; this study used a support vector machine, which is a machine learning technique [14]. There have also been studies that used analysis of snoring sounds to predict the anatomical location in the upper airway where the snoring sounds were generated [15-17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly focused on analyzing the characteristics of snoring, or distinguishing snoring from non-snoring sounds. One study reported that the classification performance of human visual scorers and a machine learning algorithm was similar in terms of automatically identifying snoring; this study used a support vector machine, which is a machine learning technique [14]. There have also been studies that used analysis of snoring sounds to predict the anatomical location in the upper airway where the snoring sounds were generated [15-17].…”
Section: Discussionmentioning
confidence: 99%
“…This model has been widely used in pattern recognition and for snoring sound analysis for SDB recognition. In [97] and [187], SVM was used for classification of oral and nasal snoring sounds. In [187], an SVM algorithm was trained and evaluated on a set of approximately 150000 snoring and non-snoring data segments.…”
Section: Sdb Detection Algorithmsmentioning
confidence: 99%
“…Specifically, the SVM classifier is easy to implement, faster in training, and better in accuracy with stability/robustness, and it performs reliably with different datasets and has fewer parameters to tune and make it operational. The scope of the work was to implement a viable system with a wellestablished classifier [38]. Based on these features and facts, we opted to incorporate SVMs into the device.…”
Section: Software Implementationmentioning
confidence: 99%